2011
DOI: 10.4269/ajtmh.2011.10-0316
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the NS1 Rapid Test and the WHO Dengue Classification Schemes for Use as Bedside Diagnosis of Acute Dengue Fever in Adults

Abstract: Because healthcare facilities in many dengue endemic countries lack laboratory support, early dengue diagnosis must rely on either clinical recognition or a bedside diagnostic test. We evaluated the sensitivity and specificity of the 1997 and 2009 World Health Organization (WHO) dengue classification schemes and the NS1 strip test in acute sera from 154 virologically confirmed dengue patients and 200 patients with other febrile illnesses. Both WHO classification schemes had high sensitivity but lacked specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
76
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 26 publications
(37 reference statements)
10
76
0
8
Order By: Relevance
“…This indicates that the probability of patient having acute dengue infection if the tests are positive is almost same as the ELISA based tests. This study finding corroborates with other studies, which have shown the PPV of rapid ICTs to be more than 85% (Pal et al, 2014;Groen et al, 2000;Shih et al, 2016).The rapid ICTs have a major advantage in that, they are easy to perform, they need less expertise and can be done within minutes (Chaterji et al, 2011).…”
Section: Resultssupporting
confidence: 91%
“…This indicates that the probability of patient having acute dengue infection if the tests are positive is almost same as the ELISA based tests. This study finding corroborates with other studies, which have shown the PPV of rapid ICTs to be more than 85% (Pal et al, 2014;Groen et al, 2000;Shih et al, 2016).The rapid ICTs have a major advantage in that, they are easy to perform, they need less expertise and can be done within minutes (Chaterji et al, 2011).…”
Section: Resultssupporting
confidence: 91%
“…Asymptomatic or flu-like DF cases are frequently under-reported, potentially causing dengue incidence to be under-estimated. Additionally, serology tests have a low specificity and sensitivity to acute dengue infection or to distinguish between primary and secondary infections of dengue (25,26). Therefore, data do not provide information on previous dengue infections, which are an important determinant in the development of DHF.…”
Section: Global and Local Clustersmentioning
confidence: 99%
“…1,12 The diagnosis of dengue infection remains challenging, because its manifestations are varied. 13,14 It is important for healthcare providers to be knowledgeable about the disease to avoid potential iatrogenic complications, including unnecessary diagnostic tests and antimicrobial therapy. …”
Section: Discussionmentioning
confidence: 99%